Implementación y configuración de un servidor proxy, utilizando software libre para mejorar la seguridad de la red, en la empresa deyesos diseños y CORNISAS CIA. LTDA. de la ciudad de Quito, en el periodo 2014-2015 - Oña Lamar, Blanca Gladys (2016)
The network security company in Deyesos Diseños y Cornisas Cía. Ltda, is an issue where external users enter without authorization, causing the network and browsing the internet is slower and caused the leakage of information is congested. The main objective of this project is to implement and configure a proxy server to improve network security and allow entry only to authorized personnel ( network users ) to external clients must be authorized or management systems to connect to a guest network (providing network password guest ) ; with these controls the enterprise network is secure. This project is supported by the kind of bibliographical research where many text files, virtual for better development of it was found. The type of field research provided important information that helped develop the project proposal for the implementation and configuration of a proxy server in the company Deyesos Diseños y Cornisas Cía. Ltda, plus the blocking of websites such as social networks, Smuts, online music, games and other lines, creating these controls allowed the network to improve its bandwidth and Internet browsing faster. To implement a proxy server Free Software Tool is used as CentOS Linux 7 and configure Squid services for locking a list of URLS that need not be visited. The management is handled by a network administrator, who will update the sites and pages to restrict access to, so they provide authentication and data integrity.